Pengaruh Efikasi Diri Terhadap Kemandirian Belajar Dengan Motivasi Belajar Sebagai Variabel Intervening - Rani Dewi Yulyani (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2021)
This study aims to examine the influence of self-efficacy on independence learning to learning motivation as an intervention variable in college students of the Ushuluddin and Adab Faculty, State Islamic University (UIN) Sultan Maulana Hasanuddin Banten. The research sample was 83 students. The data analysis technique used SEM analysis with the help of SmartPLS. Self-efficacy has an effect of 41% on the learning motivation variable and the rest is influenced by other variables. Then self-efficacy and learning motivation show an effect of 77% on the independence learning variable and the rest influenced by other variables. The results showed that self-efficacy had a positive and significant influence on independence learning, there was a positive and significant influence between the self-efficacy variable on learning motivation, and there was a positive but insignificant influence on the learning motivation variable to independence learning.